A novel NFKB1 variant in a Japanese pedigree with common variable immunodeficiency - Naoko Nakatani; Akihiro Tamura; Hiroaki Hanafusa; Nanako Nino; Nobuyuki Yamamoto; Hiroyuki Awano; Yasuhiro Tanaka; Naoya Morisada; Suguru Uemura; Atsuro Saito; Daiichiro Hasegawa; Kandai Nozu; et al. (Human Genome Variation)
Abstract Recently, heterozygous loss-of-function NFKB1 variants were identified as the primary cause of common variable immunodeficiency (CVID) in the European population. However, pathogenic NFKB1 variants have never been reported in the Japanese population. We present a 29-year-old Japanese woman with CVID. A novel variant, c.136 C > T, p.(Gln46*), was identified in NFKB1. Her mother and daughter carried the same variant, demonstrating the first Japanese pedigree with an NFKB1 pathogenic variant.